Noise Reduction Simulation on Usu Nvc Unmanned Aircraft With Capsuling Method Using Ansys 15.0 Software - Ahmad Fiqri Oemry (Trigin Publisher, 2021)
USU (University of North Sumatra) Unmaned Aerial Vehicle use DLE (data life engine) gasoline engine 30 machine as motor. The machine is classificassed as 2 stroke machine that produced major noise on vehicle. To fix the noise need study and further reaserch about acoustic or sound science. This research use capsuling method to ruduce noise factor and use rockwool as acoustic material. This study was conducted to look at the characteristics of acoustic material produced by the drone of the variation of engine speed at 3000, 4000, 5000, 6000, and 7000 rpm with a measurement distance of 1 meter. Tests done by simulation using FEM software by dividing the four major components, namely testing model airframe, engine, exhaust, and the capsuling draft. Directions were used in the simulation are horizontal, vertical, and axial (X +, X-, Y +, Y-, Z +, Z-). From the results of the simulation capsuling methods on DLE gasoline engine 30, capsuling method has no effect either to decrease the noise in the axis Y- and more dominant produces noise reduction is evenly distributed on the Y axis +. The highest noise value is generated at 7000 RPM on the Y axis and the lowest at 3000 RPM on the Y axis +. From the simulation results produced the greatest reduction in the amount of 11.9 dB on the Y axis + with a round of 3000 rpm and the smallest reduction in the amount of 0.15 dB on axis Z + with a round of 6000 rpm. The greater the rotation of the engine will be highly effective against acoustic material properties in damping vibrations that occur, so that contour noise that occurs will be scattered and produce fluctuations in the plane of unmanned aero vehicle geometry.